Respostas
respondido por:
1
Determinar a1:
an = a1 + ( n -1) . r
27 = a1 + ( 17 -1) . 3
27 = a1 + 48
27 - 48 = a1
a1 = -21
===
Determinar a3:
an = ak + ( n - k ).r
a3 = 27 + ( 3 - 17 ) . 3
a3 = 27 + ( -14 ) . 3
a3 = 27 - 42
a3 = -15
===
Determinar a5:
an = ak + ( n - k ).r
a5 = 27 + ( 5 - 17 ) . 3
a5 = 27 + ( -12 ) . 3
a5 = 27 - 36
a5 = -9
an = a1 + ( n -1) . r
27 = a1 + ( 17 -1) . 3
27 = a1 + 48
27 - 48 = a1
a1 = -21
===
Determinar a3:
an = ak + ( n - k ).r
a3 = 27 + ( 3 - 17 ) . 3
a3 = 27 + ( -14 ) . 3
a3 = 27 - 42
a3 = -15
===
Determinar a5:
an = ak + ( n - k ).r
a5 = 27 + ( 5 - 17 ) . 3
a5 = 27 + ( -12 ) . 3
a5 = 27 - 36
a5 = -9
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás